Top Management Team (TMT) Departure in Acquisition Period: Understanding The Factors That Influence The Relationship Between TMT Departure and Post-Acquisition Performance - Genial Sugianto (Business Accounting Review, 2015)
The purpose of this paper is to define the relationship between TMT Departure and post-acquisition performance and find factors that cause TMT to depart. Instead of using field works, this paper uses literature review method to answer the research question. Thus, all of relevant papers related to Merger & Acquisition and TMT departure will be included to discuss the relationship between both variables and factors behind TMT departure. Evidently, this thesis found that there is a negative effect between TMT Departure and post-acquisition performance. To put it another way, high turnover of acquired executives may cause post-acquisition performance to decrease. In order to uncover this issue further, this thesis will use 2 theories to describe eight factors that cause TMT Departure: Resource Base View (RBV) Theory and Relative Standing Theory. Thus, these factors can help acquiring management to prevent high TMT turnover.